Biogeographical variation in arthropod communities on coyote bush, Baccharis pilularis. Issue 1 (6th August 2014) - Noelia Barrios‐Garcia, Maria; Rodriguez‐Cabal, Mariano A.; González, Angélica L.; Crutsinger, Gregory M.; Didham, Raphael; Lobo, Jorge M.
Abstract A classic pattern in biogeography is the decline in species richness from lower to higher latitudes. Communities, however, can also vary with other geographical patterns, such as the abiotic gradients that occur from coastal to interior habitats. In this study, we surveyed arthropod communities and herbivore pressure on populations of a dominant shrub, Baccharis pilularis, across a 2000 km latitudinal transect to determine whether coastal versus interior location mediates arthropod responses to latitude. We found that arthropod species richness and abundance declined with increasing latitude. We also found significant coastal‐interior shifts in community composition and trophic structure. Specifically, predator and scavenger richness were two and three fold greater at coastal sites compared to interior sites, and were three‐ and six‐fold more abundant on the coast than in the interior. Herbivore pressure displayed a similar pattern, with greater abundance at lower latitudes and at coastal sites. Our results corroborate the general macroecological pattern that diversity declines with increasing latitude, and that coastal versus interior location can also shape community assemblages. We did not, however, find any interaction between latitude and location suggesting the effect of latitude on arthropod communities remains consistent inland compared to more constant coastal conditions.